Univalent Functions by Means of Chebyshev Polynomials. (16th March 2022) - Najafzadeh, Sh.; Salleh, Z.
Abstract : The primary motivation of the paper is to define a new class C h δ α, β, γ which consists of univalent functions associated with Chebyshev polynomials. For this class, we determine the coefficient bound and convolution preserving property. Furthermore, by using subordination structure, two new subclasses of C h δ α, β, γ are introduced and denoted by M λ 1, λ 2, s and N λ 1, λ 2, s, respectively. For these subclasses, we obtain coefficient estimate, extreme points, integral representation, convexity, geometric interpretation, and inclusion results. Moreover, we prove that, under some restrictions on parameters, C h δ α, β, γ = N λ 1, λ 2, s .